The Emergence of Black Jews in France - Aurélien Mokoko Gampiot (Religions)
For the past three decades, Black Jews in France have made their presence manifest. These believers identify as African, West Indian, or biracial, and are either converts or native Jews. They may either assert their faith from within the institutions of French Jewry, or claim their Jewishness without practicing Judaism. They have widely different backgrounds, but share a common need for identity reconstruction. This paper aims to discuss this Africana minority within the broader French Jewish community, taking into account its relation to the majority. What is the positioning of Black Jews as French citizens or residents? How do they perceive themselves when reading the Torah and through the gaze of their fellow White Jews? What is their place within the global Jewish world? Such are the questions this paper will try to address, building on fifteen years of fieldwork in France and assessing their involvement in French Jewry and its impact with regard to participation, integration, legitimacy, and conflicts.